2022
DOI: 10.1093/sleep/zsac210
|View full text |Cite
|
Sign up to set email alerts
|

The effect of obstructive sleep apnea therapy on cardiovascular autonomic function: a systematic review and meta-analysis

Abstract: Study Objectives Autonomic function is impaired in obstructive sleep apnea (OSA) and may mediate the association between OSA and cardiovascular risk. We investigated the effect of OSA therapy on autonomic function through a systematic review and meta-analysis of intervention studies. Methods A systematic search using three databases (Medline, Embase, and Scopus) was performed up to December 9, 2020. Studies of OSA patients ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…However, a key gap in existing HRV analysis is that there are no reference values and the combination of HRV metrics to determine clinically significant autonomic dysfunction in the OSA population, thus limiting their generalisability towards monitoring treatment efficacy in clinical practice (Dissanayake et al, 2022). The attempt to estimate standard short‐term and long‐term HRV norms stratified by age and sex would accelerate the application of HRV.…”
Section: The Technology and Limitations Of Hrv Analysis In Osamentioning
confidence: 99%
See 2 more Smart Citations
“…However, a key gap in existing HRV analysis is that there are no reference values and the combination of HRV metrics to determine clinically significant autonomic dysfunction in the OSA population, thus limiting their generalisability towards monitoring treatment efficacy in clinical practice (Dissanayake et al, 2022). The attempt to estimate standard short‐term and long‐term HRV norms stratified by age and sex would accelerate the application of HRV.…”
Section: The Technology and Limitations Of Hrv Analysis In Osamentioning
confidence: 99%
“…Summarised findings of included studies in terms of HRV in treatments for OSA are shown in Table 1. A recent meta-analysis found that the differences of autonomic modulation assessed by HRV including global, sympathetic, and parasympathetic HRV did not reach statistical significance before and after OSA treatment, but OSA treatment can reduce sympathetic activity as measured by muscle sympathetic nerve activity (Dissanayake et al, 2022). This discrepancy may result from poor control of the condition, affecting HRV measurement, and various methods of signal processing and analysis across studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other nonlipoprotein biomarkers of metabolic syndrome are summarized in Table 2[83–90,91 ▪ ,92,93–100,101 ▪ ,102,103–107].…”
Section: Novel Cardiovascular Risk Factors and Metabolic Syndromementioning
confidence: 99%
“…This is associated with autonomic dysregulation expressed as increased sympathetic discharge and a shift in heart rate variability from high to low‐frequency bands (related to sympathetic overactivity) (Floras & Ponikowski, 2015). Recent studies have shown that OSA therapy improved autonomic function measures, which may reduce the risk CVD through decreased sympathetic activity (Barthelemy et al., 2022; Dissanayake et al., 2022). These observations further reinforce the major role of excessive sympathetic activity in the pathogenesis of OSA and its associated end‐organ morbidities.…”
Section: Introductionmentioning
confidence: 99%